Provincial convention center - Masikip, Jose E. Jr. (Manila : National University, 2002)
Most people look for the place where the can formulate a party or assembly on having any official gathering of delegate on the convention center. This suggests that the center plays a big part which can designed and implemented to the province of Antipolo.